Fermentation - Processes, Benefits and Risks 2021
DOI: 10.5772/intechopen.96542
|View full text |Cite
|
Sign up to set email alerts
|

From Food Waste to Volatile Fatty Acids towards a Circular Economy

Abstract: The food industrial sector generates large amounts of waste, which are often used for animal feed, for agriculture or landfilled. However, these wastes have a very reach composition in carbon and other compounds, which make them very attractive for valorization through biotechnological processes. Added value compounds, such as volatile fatty acids (VFAs), can be produced by anaerobic fermentation using pure cultures or mixed microbial cultures and food waste as carbon source. Research on valuable applications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…The properties of these acids are shown in Table 2. They are potential renewable carbon sources in a variety of biological processes, such as biopolymer formation, biological nutrient removal, and creation of bioenergy, and have a wide range of applications, such as food additives, pharmaceutical products, cosmetics, and chemical precursors [59,60]. In general, the distribution of fermentation products reflects prevailing metabolic pathways [61].…”
Section: Acidogenic Fermentationmentioning
confidence: 99%
See 1 more Smart Citation
“…The properties of these acids are shown in Table 2. They are potential renewable carbon sources in a variety of biological processes, such as biopolymer formation, biological nutrient removal, and creation of bioenergy, and have a wide range of applications, such as food additives, pharmaceutical products, cosmetics, and chemical precursors [59,60]. In general, the distribution of fermentation products reflects prevailing metabolic pathways [61].…”
Section: Acidogenic Fermentationmentioning
confidence: 99%
“…Wang et al (2014) [69] observed that sCOD produced at pH 4 and uncontrolled pH was higher than that produced at pH 5 and pH 6 during VFA production from FW. However, most microorganisms cannot survive in extremely acidic (pH = 3) or alkaline (pH = 12) conditions; thus, it is necessary to maintain an optimal pH for inducing acidification depending on the type of wet waste and acids of interest [60]. Previous research reported that the highest VFA yield was achieved under slightly acid-neutral conditions (pH 5.5-7.0).…”
Section: Factors Affecting Acidogenic Fermentationmentioning
confidence: 99%
“…VFAs are short-chain fatty acids with a low molecular weight that consist of two to six carbon atoms and that are mostly derived from fossil fuels using chemical routes, leading to serious negative health and environmental impacts [ 93 , 94 ]. Thus, the replacement of these processes by biological ones such as by using pure or mixed microbial cultures or by using renewable carbon sources is gaining more attention [ 91 , 92 , 94 , 95 ]. This strategy represents a cost-effective and environmentally friendly alternative for VFAs production [ 91 ].…”
Section: Volatile Fatty Acidsmentioning
confidence: 99%
“…The volatile fatty acids (VFAs) are valuable compounds with a high market demand and with several applications, namely as precursors for bioplastics (e.g., polyhydroxyalkanoates (PHA)), biogas, biohydrogen, and biodiesel production as well as for nutrient removal (Figure 3) [91,92]. The possibility of using wastewater as an alternative source of energy for he recently emerged as a feasible approach.…”
Section: Volatile Fatty Acidsmentioning
confidence: 99%
See 1 more Smart Citation